1994
DOI: 10.2307/1382558
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Diets of Juvenile and Adult Hoary Bats, Lasiurus cinereus

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. American Society of Mammalogists is collaborating with JSTOR to digitize, preserve and extend access to Journal of Mammalogy.The diets of hoary bats (Lasiurus cinereus) within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 13 publications
(1 reference statement)
0
26
0
1
Order By: Relevance
“…These differences could result from differences in diet (Barclay 1985, Reimer et al 2010 or foraging habitat (i.e., different association with standing water and aquatic foodwebs; Britzke et al 2009, Sellick et al 2009 or the combination of the two. The diets of hoary bats and silver-haired bats on the summering grounds are slightly different, as are the diets of sub-adult hoary bats (at least for the first two weeks postvolancy; Rolseth et al 1994). Although both species are opportunistic aerial-hawkers that eat similar types of insects, silver-haired bats and sub-adult hoary bats tend to eat smaller prey items than adult hoary bats (Barclay 1985, Rolseth et al 1994.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences could result from differences in diet (Barclay 1985, Reimer et al 2010 or foraging habitat (i.e., different association with standing water and aquatic foodwebs; Britzke et al 2009, Sellick et al 2009 or the combination of the two. The diets of hoary bats and silver-haired bats on the summering grounds are slightly different, as are the diets of sub-adult hoary bats (at least for the first two weeks postvolancy; Rolseth et al 1994). Although both species are opportunistic aerial-hawkers that eat similar types of insects, silver-haired bats and sub-adult hoary bats tend to eat smaller prey items than adult hoary bats (Barclay 1985, Rolseth et al 1994.…”
Section: Discussionmentioning
confidence: 99%
“…The diets of hoary bats and silver-haired bats on the summering grounds are slightly different, as are the diets of sub-adult hoary bats (at least for the first two weeks postvolancy; Rolseth et al 1994). Although both species are opportunistic aerial-hawkers that eat similar types of insects, silver-haired bats and sub-adult hoary bats tend to eat smaller prey items than adult hoary bats (Barclay 1985, Rolseth et al 1994. However, the stomachcontent analysis of 54 of the bats used in this study revealed few dietary differences among species, age and sex classes (Reimer et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the late summer increase in mortality is not likely explained by a concurrent shift in diet or habitat use of resident adult bats. Recently fledged juvenile bats have been reported to have reduced abilities to echolocate and fly compared to adults (Gould 1955, Buchler 1980, Timm 1989, Rolseth et al 1994; thus they may be more susceptible to colliding with turbines or other objects (Manville 1963). Juvenile bats also change diets and increase home range size over the first several weeks post fledging (Rolseth et al 1994), thereby possibly making them more susceptible to turbine collision during post fledging.…”
Section: Department Of Energy 2002)mentioning
confidence: 99%
“…Recently fledged juvenile bats have been reported to have reduced abilities to echolocate and fly compared to adults (Gould 1955, Buchler 1980, Timm 1989, Rolseth et al 1994; thus they may be more susceptible to colliding with turbines or other objects (Manville 1963). Juvenile bats also change diets and increase home range size over the first several weeks post fledging (Rolseth et al 1994), thereby possibly making them more susceptible to turbine collision during post fledging. However, the increase in mortality during late summer cannot be explained by a shift in habitat use by juveniles or an increase in the number of young, inexperienced bats that had recently begun flying.…”
Section: Department Of Energy 2002)mentioning
confidence: 99%
“…Among insectivorous bats, age-related shifts in both foraging habitat (Adams, 1996) and diet (Rolseth et al, 1994;Hamilton and Barclay, 1998) have been described, although these studies have focused on differences between young bats (i.e., one year old or less) and adults. Changes in foraging ecology may also occur as adult bats age.…”
Section: Introductionmentioning
confidence: 99%